SARS-CoV-2 Infection in Fully Vaccinated Individuals of Old Age Strongly Boosts the Humoral Immune Response - Müller, Lisa; Andrée, Marcel; Ostermann, Philipp Niklas; Jazmati, Nathalie; Flüh, Greta; Fischer, Johannes C.; Bölke, Edwin; Heger, Eva; Vanshylla, Kanika; Klein, Florian; Wisplinghoff, Hilmar; Schaal, Heiner; et al. (Frontiers in Medicine, 2021)
Prophylactic vaccination against SARS-CoV-2 is one of the most important measures to contain the COVID-19 pandemic. Recently, break-through infections following vaccination against this virus have been reported. Here, we describe the humoral immune response of break-through infections in fully vaccinated individuals of old age from an outbreak in a nursery home. In cooperation with the local health authority, blood samples from fully vaccinated and infected as well as fully vaccinated and uninfected residents of the nursery home were collected four weeks after the onset of the outbreak. The humoral immune response was determined in a neutralisation assay with replication-competent virus isolates and by a quantitative ELISA. In this outbreak a total of 23 residents and four health care workers were tested positive for SARS-CoV-2. Four residents were unvaccinated, including one with a severe course of disease who later deceased. Despite their old age, all vaccinated residents showed no or only mild disease. Comparison of the humoral immune response revealed significantly higher antibody levels in fully vaccinated infected individuals compared to fully vaccinated uninfected individuals (p<0.001). Notably, although only a minority of the vaccinated uninfected group showed neutralisation capacity against SARS-CoV-2, all vaccinated and infected individuals showed high-titer neutralisation of SARS-CoV-2 including the alpha and beta variant. Large SARS-CoV-2 outbreaks can occur in fully vaccinated populations, but seem to associate with mild disease. SARS-CoV-2 infection in fully vaccinated individuals is a strong booster of the humoral immune response providing enhanced neutralisation capacity against immune evasion variants.